EXPLORATION OF PH MEASUREMENT WITH NATURAL AND CHEMICAL INDICATORS - Nazwar, Akhsan Pradika (Journal of Natural Sciences and Learning, 2025)
pH measurement is an important method in chemical analysis to determine the level of acidity or alkalinity of a solution. This research aims to explore pH measurement using natural and chemical indicators. The research method involves the process of preparing indicators, measuring the pH of acid- base solutions, and comparative analysis of the results. The natural indicators used come from plant extracts such as turmeric, beetroot, butterfly pea flower, hibiscus flower, orange, while the chemical indicators are litmus paper and pH indicators. Extraction of natural indicators is carried out by a simple method using water as a solvent. The measurement results show that natural indicators provide a clear color change response in a certain pH range, although their sensitivity is lower than chemical indicators. Chemical indicators provide more precise and consistent results, but require higher costs and have potential environmental impacts. This research highlights the potential of natural indicators as environmentally friendly alternatives in pH measurement, especially for educational and small-scale applications. Thus, natural indicators can be a more economical and sustainable solution. The results of this research contribute to the development of a pH measurement method that is easy, cheap and environmentally friendly The purpose of this study is to find out natural materials that can be used as a substitute for chemical indicators such as litmus paper. The results of the research we conducted show that chemical indicators are more accurate compared to natural indicators.   .